Polyamide nanofiltration membrane with highly uniform sub-nanometre pores for sub-1 Å precision separation - Yuanzhe Liang (Nature Portfolio, 2020)
Separating molecules or ions with sub-Angstrom scale precision is important but technically challenging. Here, the authors demonstrate that precise solute-solute separation can be achieved using polyamide membranes formed via surfactant-assembly regulated interfacial polymerization.